A Method for Routine Analysis of Urinary 4, 4′‐methylenebis (2‐chloroaniline) by Gas Chromatography‐Electron Capture Detection. Issue 5 (22nd November 2014) - Takeuchi, Akito; Namera, Akira; Sakui, Norihiro; Yamamuro, Kenji; Kawai, Toshio; Sumino, Kimiaki
Abstract : A Method for Routine Analysis of Urinary 4, 4'‐methylenebis (2‐chloroaniline) by Gas Chroma‐tography‐Electron Capture Detection: Akito TAKEU‐CHI, et al . Osaka Occupational Health Service Center, Japan Industrial Safety and Health Association— Objectives: The purpose of this study was to develop a simple and cost‐effective method for the determination of urinary 4, 4'‐methylenebis (2‐chloroaniline) (MBOCA) by gas chromatography‐electron capture detection (GC‐ECD) for biological monitoring of occupational exposure to MBOCA. Methods: MBOCA was prepared by liquidliquid extraction after alkaline hydrolysis, derivatized with N ‐methyl‐bis (trifluoroacetamide) and then analyzed using GC‐ECD. The proposed method was validated in accordance with the US Food and Drug Administration guidance. Results: The calibration curve showed linearity in the range 1–100 μg/ l, with a correlation coefficient of >0.999. The limits of detection and quantification were 0.3 μg/ l and 1 μg/ l, respectively. The recovery was 94−99%. Intraday accuracy, expressed as the deviation from the nominal value, was 90.5−100.3%, and intraday precision, expressed as the relative standard deviation, was 0.3−2.4%. Interday accuracy and precision were 87.8−100.2% and 0.3−4.1%, respectively. Conclusions: The proposed method is a simple and cost‐effective method suitable for routine analyses and could be useful for biological monitoring of occupational exposure to MBOCA.